Developing Religious Moderation Perspectives and the Internalization ofEcotheology: Efforts to Build Religious and Ecological Awareness in theBorder Region of Natuna Regency - Putri R. Hariswati (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2025)
This study aims to analyze the development of religious moderation perspectives and the internalization of ecotheology as strategies for building religious and ecological awareness in the border region of Natuna Regency. As a strategic archipelagic area, Natuna faces various ecological pressures such as coral reef degradation, coastal abrasion, and marine pollution driven by both local and transboundary activities. On the other hand, the people of Natuna possess a strong religious character and are deeply connected to their coastal environment, making religious values a potential moral foundation for shaping ecological behavior. Using a qualitative-descriptive approach, this study examines the integration of religious moderation—grounded in principles of balance, tolerance, and cultural adaptation—with Islamic ecotheology, which emphasizes tauhid, khalifah, and amanah as spiritual foundations for environmental ethics. The findings indicate that the internalization of ecological values through religious channels is more readily accepted by the community, particularly through the roles of religious instructors, traditional leaders, and educational institutions. Programs such as Ecology-Oriented Religious Instructor Training, the Green Mosque Movement, and local wisdom–based preaching have proven relevant in strengthening environmental awareness among the Natuna community. This study highlights that integrating religious moderation and ecotheology can serve as a model for empowering coastal communities and as a strategy for socio-ecological resilience in border regions. The study recommends strengthening cross-sector collaboration, enhancing ecological literacy, and developing environmentally friendly curricula in schools and madrasahs.